Benthic microalgal communities in the inner part of the Bahía Blanca estuary (Argentina): a preliminary study - Parodi, Elisa Rosalia (2002)
The intertidal zone of the inner part of the Bahía Blanca estuary, Argentina is characterised by the presence of muddy tidal flats and salt marshes, habitats for burrowing crabs and halophytic plants. The surface layer of the sediments is composed of silt and clay. The sediments are substrate for the proliferation of benthic microalgal communities. The aim of this study was to analyse qualitatively the species composition of these communities and their role in the stabilisation of the sediments. Samples came from two stations: Puerto Cuatreros and Villarino Viejo. Puerto Cuatreros is an old pier without harbour activities closer than Villarino Viejo to the harbour zone affected by dredging. Both stations showed similar physical and chemical parameters. In addition, the benthic microalgal communities at both stations were comprised of cyanophytes and diatoms. The main difference between the two stations was the relative frequency of the algae—cyanophytes were predominant in Villarino Viejo while diatoms predominated in Puerto Cuatreros. Presumably, the difference was due to the major disturbance of the first due to deposition of particles of the fluid mud layer produced by the nearby dredging. Major species of cyanophytes were Microcoleus chtonoplastes and Oscillatoria limosa. Diatom assemblages were very diverse since the estuarine characteristics of the system allow the coexistence of marine, freshwater and estuarine species; also some of these species may be present in the plankton community.